Computerized evaluation and advice in swimming - Persyn, U.; van Tilborgh, L.; Daly, D.; Colman, V.; Vijfvinkel, D. V.; Verhetsel, D. (Swimming Science V, 1988)
In most Western countries, government support cannot be expected for extensive evaluations of large numbers of elite swimmers in a laboratory. For this reason, research in the Leuven Evaluation Center for Swimmers has been directed toward the development of a user-friendly system, allowing an expert to make rapid diagnoses and to provide advice at poolside. Attention is given to simple observation and measuring instrumentation as well as to personal computer (PC) software. The PC allows hydromechanical, kinanthropometric, physiological, and other data to be used for the evaluation of swimmers and for the education of swimming consultants. In order to select information relevant to performance, a review was made of effective instruction for correcting the movement and/or improving physical characteristics, and thus resulting in enhanced swimming performances. Diverse categories of relevant information have been collected in the Evaluation Center on 600 elite swimmers (10 to 22 years old) from various countries.